Emissions of wood pelletization and bioenergy use in the United States - Tran, Huy; Juno, Edie; Arunachalam, Saravanan (Renewable energy, 2023)
Despite a significant increase in United States biomass energy sector activity, including domestic bioenergy deployment and wood pellet production for overseas exports, the associated criteria pollutant emissions are not well quantified in current regulatory emissions inventories. We present an updated U.S. emissions inventory, with emphasis on wood-based biomass pretreatment (e.g., drying, condensing, storage of wood pellet) and the use of biomass for energy generation. As a significant number of wood pellet production facilities are not included in current inventories, we find that this sector's emissions could be potentially underestimated by a factor of two. Emissions from biomass-based facilities are on average up to 2.8 times higher than their non-biomass counterparts per unit energy. We estimate that 2.3 million people live within 2 km of a biomass facility and who could be subject to adverse health impacts from their emissions. Overall, we find that the bioenergy sector contributes to about 3–17% of total emissions from all energy, i.e., electric and non-electric generating facilities in the U.S. We also review some drivers of bioenergy expansion, such as various feedstocks and technologies deployed with an emphasis on wood-based bioenergy and discuss their implications for future air quality and health impacts.